Šiaulių ekonomijos XVIII a. pabaigos-XIX a. I trečdalio baudžiavinių ūkių koreliacinė regresinė analizė - Pamerneckis, Stasys (Lietuvos istorijos studijos, 1998)
Formalysed statistical analysis permitted to conclude agricultural and extensive character of the production in the Šiauliai economy.The richest peasant farms had more possibilities to include in the market production - showed analysis of the historical record office materials.The results of this research confirm too, that the level of feudal rent in the end of 18th c. depended on the general economical level of Lithuanian corvee-peasant farms.